A Molecular Study of Pediatric Spindle and Sclerosing Rhabdomyosarcoma: Identification of Novel and Recurrent VGLL2-related Fusions in Infantile Cases. (February 2016) - Alaggio, Rita; Zhang, Lei; Sung, Yun-Shao; Huang, Shih-Chiang; Chen, Chun-Liang; Bisogno, Gianni; Zin, Angelica; Agaram, Narasimhan P.; LaQuaglia, Michael P.; Wexler, Leonard H.; Antonescu, Cristina R.
Abstract : Sclerosing rhabdomyosarcoma (ScRMS) and spindle cell rhabdomyosarcoma (SRMS) have been recently reclassified as a stand-alone pathologic entity, separate from embryonal RMS. Genetically, a subset of the congenital cases display NCOA2 gene rearrangements, whereas tumors occurring in older children or adults harbor MYOD1 gene mutations with or without coexisting PIK3CA mutations. Despite these recent advances, a significant number of tumors lack known genetic alterations. In this study we sought to investigate a large group of pediatric SRMS/ScRMS, spanning a diverse clinical and pathologic spectrum, by using a combined fluorescence in situ hybridization, targeted DNA, and whole-transcriptome sequencing methodology for a more definitive molecular classification. A total of 26 SRMS and ScRMS cases were selected from the 2 participating institutions for the molecular analysis. Ten of the 11 congenital/infantile SRMS showed recurrent fusion genes: with novel VGLL2 rearrangements seen in 7 (63%), including VGLL2-CITED2 fusion in 4 and VGLL2-NCOA2 in 2 cases. Three (27%) cases harbored the previously described NCOA2 gene fusions, including TEAD1-NCOA2 in 2 and SRF-NCOA2 in 1. All fusion-positive congenital/infantile SRMS patients with available long-term follow-up were alive and well, none developing distant metastases. Among the remaining 15 SRMS patients older than 1 year, 10 (67%) showed MYOD1 L122R mutations, most of them following a fatal outcome despite an aggressive multimodality treatment. All 4 cases harboring coexisting MYOD1 / PIK3CA mutations shared sclerosing morphology. All 5 fusion/mutation-negative SRMS cases presented as intra-abdominal or paratesticular lesions. Abstract : Supplemental Digital Content is available in the text.